Respuesta :
The general equation of a quadratic is expressed as y = ax^2+bx+c. To
convert the general equation to vertex form, we need to obtain this form:
(y- k)= a(x - h)^2
This could be done by using completing the square method.
y = –3x^2 – 12x – 2
y + 2 = –3(x^2 + 4x)
y + 2 -12 = –3(x^2 + 4x + 4)
y - 10 = -3(x+2)^2
Therefore, the answer is the first option.
(y- k)= a(x - h)^2
This could be done by using completing the square method.
y = –3x^2 – 12x – 2
y + 2 = –3(x^2 + 4x)
y + 2 -12 = –3(x^2 + 4x + 4)
y - 10 = -3(x+2)^2
Therefore, the answer is the first option.